2017
DOI: 10.5115/acb.2017.50.4.247
|View full text |Cite
|
Sign up to set email alerts
|

Morphological classification and comparison of suboccipital muscle fiber characteristics

Abstract: In an attempt to clarify the function of the suboccipital muscles, we performed morphological observation of the suboccipital muscles for variations in the muscle belly and compared the morphology of their muscle fibers in terms of cross-sectional area by immunostaining with anti-myosin heavy chain antibodies. The cadavers of 25 Japanese individuals were used: 22 for morphological examinations and three for histological examinations. Among samples of the rectus capitis posterior major muscle (RCPma) and rectus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…These are four paired muscles (rectus capitis posterior major, rectus capitis posterior minor, obliquus capitis superior, and obliquus capitis inferior). Unilateral contraction of these muscles induces head rotation, and bilateral contraction causes head extension (Yamauchi et al, 2017). These muscles have a high muscle spindle density that not only allows flexible movement, but also act as specific sensory receptors (Kulkarni et al, 2001).…”
Section: Musclesmentioning
confidence: 99%
See 2 more Smart Citations
“…These are four paired muscles (rectus capitis posterior major, rectus capitis posterior minor, obliquus capitis superior, and obliquus capitis inferior). Unilateral contraction of these muscles induces head rotation, and bilateral contraction causes head extension (Yamauchi et al, 2017). These muscles have a high muscle spindle density that not only allows flexible movement, but also act as specific sensory receptors (Kulkarni et al, 2001).…”
Section: Musclesmentioning
confidence: 99%
“…These muscles have a high muscle spindle density that not only allows flexible movement, but also act as specific sensory receptors (Kulkarni et al, 2001). Therefore, these muscles allow to control delicate movements in atlanto-occipital (C1-C0) and atlanto-axial (C1-C2) joint (Yamauchi et al, 2017). However, sustained and excessive stress in the cervical spine resulted from incorrect posture causes problems in these muscles.…”
Section: Musclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound imaging has gained relevance in recent years in the evaluation of cervical spine musculature. In fact, different studies reported the ability of ultrasound imaging to investigate deep neck extensors, such as the cervical multifidus [ 14 ] and suboccipital [ 15 ] muscles. No previous study has investigated cervical muscle morphology in individuals with TMD.…”
Section: Introductionmentioning
confidence: 99%
“…Agten et al [45] reported that the multifidus is a postural muscle that provides stability in the lumbar vertebral column because of its predominance of slow-twitch fibers. Yamauchi et al [49] observed that RCPmi and OCS have at least two-fold greater cross-sectional areas of slow-twitch fibers than fast-twitch fibers in human cadavers, and that OCI has a significantly larger cross-sectional area of fast-twitch fibers than other suboccipital muscles. Therefore, they suggested that the RCPmi and OCS may provide more force than the RCPma and OCI and act as antigravity agonist muscles of the head.…”
Section: Suboccipital Muscles and Dizzinessmentioning
confidence: 99%